Implementation of green tourism policy strategy of PT Taco Casa Bali through corporate social responsibility - I Ketut Purna Wirananta; Ni Luh Ayu Kartika Yuniastari Sarja (International Journal of Green Tourism Research and Applications, 2020)
Purpose: This article is to explain the implementation of corporate social responsibility (CSR) at PT Taco Casa Bali in carrying out its social and environmental responsibilities to support green tourism.Research methods: This study is done in a qualitative method in which the data collection was carried out through library techniques and field research in the form of observation and interviews with the Corporate Operations Manager of PT Taco Casa Bali.Results and discussion: The result of the study shows that the CSR implementation of PT Taco Casa Bali is in the form of fixed and unscheduled activities that support green tourism policies and regulations (people, planet, and profit).Conclusion: The research is an illustration of how CSR practices in a company should be maximally realized so that in the end both the business and the business environment.